How does hospitalization affect continuity of drug therapy: an exploratory study - Blozik E; Signorell A; Reich O (Dove Medical Press, 2016)
Eva Blozik,1–3 Andri Signorell,1 Oliver Reich1 1Department of Health Sciences, Helsana Group, Zürich, Switzerland; 2Department of Primary Medical Care, University Medical Centre Hamburg-Eppendorf, Hamburg, 3Department of Medicine, University Medical Centre Freiburg, Freiburg im Breisgau, Germany Introduction: Transitions between different levels of health care, such as hospital admission and discharge, pose a significant threat to the quality and continuity of medication therapy. This study aims to explore the role of hospitalization on medication changes as patients are transferred from and back to ambulatory care.Methods: Secondary analysis of claims data from Swiss residents with basic health insurance at the Helsana Group was performed. We evaluated medication invoices of patients who were hospitalized in a Swiss private hospital group in the year 2013. Medication changes were defined as discontinuation, new prescription, or change in the Anatomical Therapeutic Chemical (ATC) Classification System level 4, which is equivalent to a change in the chemical/therapeutic/pharmacological subgroup. Multiple Poisson regression analysis was applied to evaluate whether medication change was predicted by socioeconomic or clinical patient characteristics or by a system factor (physician dispensing of medication allowed in canton of residence).Results: We investigated a total of 10,123 hospitalized patients, among whom a mean number of 3.85 (median 3.00) changes were identified. Change most frequently affected antihypertensives, analgesics, and antirheumatics. If patients were enrolled in a managed care plan, they were less likely to undergo changes. If a patient resided in a canton, in which physicians were allowed to dispense medication directly, the patient was more likely to experience change.Conclusion: There is considerable change in medication when patients shift between ambulatory and inpatient health care levels. This interruption of medication continuity is in part desirable as it responds to clinical needs. However, we hypothesize that there is also a significant proportion of change due to unwarranted factors such as financial incentives for change of products. Keywords: medication, prescribing, safety, hospital, admission, discharge